Stock Valuation on Energy Sector Companies within IDX High Dividend 20 Index Year 2025 - Argari Alpharianto; Dadan Rahadian (Asean International Journal of Business, 2026)
The energy sector constitutes one of the largest component of the IDX High Dividend 20 Index for 2025, comprising five companies such as ADRO, AKRA, ITMG, PGAS, and PTBA. Over the past three years, this sector has exhibited the strongest upward trajectory, achieving a cumulative growth rate of 136% and an average annual return of 18.52% among these companies, thereby underscoring its appeal to dividend-seeking investors. This study examines the intrinsic value of five said companies using the Dividend Discount Model (DDM) and two relative valuation metrics (EV/EBITDA and Price to Earnings Ratio or PER). Under the DDM framework, ADRO, ITMG, and PTBA appear as undervalued relative to their intrinsic value, while AKRA and PGAS appear overvalued. When benchmarked against the sector’s mean EV/EBITDA and PER, all five companies register as undervalued. However, comparing company multiples to the sector median EV/EBITDA recasts AKRA as overvalued, PTBA as fairly valued, and the remaining three as undervalued. A parallel comparison using the sector median PER identifies AKRA as overvalued, with the other four companies maintaining undervalued status. On the basis of these findings, investors may prioritize acquisitions of ADRO and ITMG shares, given their consistent undervaluation across all models. AKRA and PGAS warrant caution due to overvaluation in at least one metric. PTBA merits continued monitoring, as it is fairly valued on an EV/EBITDA basis yet undervalued when assessed by PER and DDM valuation.